2020
DOI: 10.1093/carcin/bgaa018
|View full text |Cite
|
Sign up to set email alerts
|

Parabacteroides distasonis attenuates tumorigenesis, modulates inflammatory markers and promotes intestinal barrier integrity in azoxymethane-treated A/J mice

Abstract: Imbalance of the gut microbial community promotes inflammation and colorectal cancer (CRC). Previously, we demonstrated that freeze-dried Parabacteroides distasonis (Pd) suppressed obesity-driven colorectal tumorigenesis in mice. Here, we investigated if Pd could suppress the development of colon tumors in mice independent of obesity. Six-week-old male A/J mice were assigned to receive: (i) chow diet (CTR); (ii) chow with 0.04% wt/wt freeze-dried Pd (Pd-Early) or (iii) chow diet before switching to 0.04% Pd di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 36 publications
5
71
2
Order By: Relevance
“…Studies by other researchers have suggested that P. distasonis has anti-inflammatory and antitumor properties mediated by the reduction of signaling via TLR4, MYD88, and Akt and the stimulation of apoptosis. 86 These results are in agreement with observations of reduced microbiome levels of P. distasonis in mouse models of colorectal cancer. 44 In a study by Koh et al 86 that was previously noted for revealing P. distasonis effect on the expression of tight junction proteins, the same mice were later treated with the carcinogen azoxymethane (AOM).…”
Section: Protective Role In Colorectal Cancersupporting
confidence: 90%
See 2 more Smart Citations
“…Studies by other researchers have suggested that P. distasonis has anti-inflammatory and antitumor properties mediated by the reduction of signaling via TLR4, MYD88, and Akt and the stimulation of apoptosis. 86 These results are in agreement with observations of reduced microbiome levels of P. distasonis in mouse models of colorectal cancer. 44 In a study by Koh et al 86 that was previously noted for revealing P. distasonis effect on the expression of tight junction proteins, the same mice were later treated with the carcinogen azoxymethane (AOM).…”
Section: Protective Role In Colorectal Cancersupporting
confidence: 90%
“…Multiple researchers have identified that levels of P. distasonis in stool are inversely correlated to the presence of intestinal tumors. 101 Koh et al 86 determined that P. distasonis membrane fractions were responsible for suppressing the production of proinflammatory cytokines in a colon cancer cell line. Studies by other researchers have suggested that P. distasonis has anti-inflammatory and antitumor properties mediated by the reduction of signaling via TLR4, MYD88, and Akt and the stimulation of apoptosis.…”
Section: Protective Role In Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…When fed to BALB/C mice, P. distasonis could reduce the severity of intestinal inflammation of acute and chronic colitis (Kverka et al, 2011). Likewise, Koh et al (2020) has reported the beneficial role of P. distasonis in attenuating colonic tumorigenesis and maintaining intestinal epithelial barrier in azoxymethane (AOM)-treated mice (Koh et al, 2020).…”
Section: The Underlying Molecular Mechanisms Of Colon Carcinogenesis mentioning
confidence: 99%
“…Findings from prior research show that Parabacteroides distasonis, Ruminiclostridium 5, and Clostridium leptum are associated with positive health states, whereas reduced levels are associated with negative health states. Oral administration of Parabacteroides distasonis, for example, suppresses colon tumorigenesis and sustains epithelial barrier function in a mouse model (Koh et al 2019). In addition, recovery from sleep fragmentation (Maki et al 2020) is associated with increased relative abundance of Ruminiclostridium 5.…”
Section: Body Weights and Food Consumptionmentioning
confidence: 99%